Solving Solutions in Raising the GRDP of Batam City Based on Theoretical and Empirical Evidence - Venessa Venessa (Green Publisher Indonesia, 2021)
This paper aims to research the current GDP growth of Batam and provide alternative solutions to the city regarding to the several possible steps that can be taken in terms of raising the GDP of Batam city. Substantial evidence was shown that proves that Batam has not reached its possible target of GRDP growth. Several operable solutions were provided in this paper, all those that ultimately leads to pushing more citizens to open up new business which leads to new job creations, the increased number of investors that are willing to put money in Batam, and the increased productivity and quality of our human resources. To conclude shortly, this paper provided information that can describe the performance of the regional economy, evaluated development results, contributed to the making of regional policies or plans, and provided operable solutions in order to raise the GDP of Batam which, in the long run, is expected to increase the quality of life in Batam.